1997
DOI: 10.1029/97wr02135
|View full text |Cite
|
Sign up to set email alerts
|

A diffusion‐based interpretation of tetrachloroethene and trichloroethene concentration profiles in a groundwater aquitard

Abstract: Abstract. Analysis of subsurface soil cores from the site of a field-scale groundwater remediation experiment at Dover Air Force Base, Delaware, has revealed that tetrachloroethene (PCE) and trichloroethene (TCE) contamination extends into an aquitard underlying a groundwater aquifer. The site location is well doWngradient of the locations of contaminant release, and the aquitard contamination is believed to have begun when contaminated groundwater first arrived in the overlying aquifer. Using independent esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
82
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 91 publications
(84 citation statements)
references
References 23 publications
2
82
0
Order By: Relevance
“…These authors reported an average tortuosity value 3.67 times higher than that assumed in our prior work, and note that tortuosity values may not be known to better than a factor of 4 without specific evaluation. Because of remaining uncertainties regarding the applicability of repacked column results to our field situation, and more important, for better direct comparison with our prior two-step modeling results [Ball et al, 1997a], we use our prior tortuosity estimates (X = 1.4) in this work. In this regard, we note that the time associated with any particular forensically estimated boundary concentration will scale inversely with effective diffusivity, i.e., as would be associated with constant values of Dt/R (D is the diffusion coefficient, t is time, and R is the retardation factor) for any given length scale of diffusion.…”
Section: Field Sampling and Analysismentioning
confidence: 99%
See 4 more Smart Citations
“…These authors reported an average tortuosity value 3.67 times higher than that assumed in our prior work, and note that tortuosity values may not be known to better than a factor of 4 without specific evaluation. Because of remaining uncertainties regarding the applicability of repacked column results to our field situation, and more important, for better direct comparison with our prior two-step modeling results [Ball et al, 1997a], we use our prior tortuosity estimates (X = 1.4) in this work. In this regard, we note that the time associated with any particular forensically estimated boundary concentration will scale inversely with effective diffusivity, i.e., as would be associated with constant values of Dt/R (D is the diffusion coefficient, t is time, and R is the retardation factor) for any given length scale of diffusion.…”
Section: Field Sampling and Analysismentioning
confidence: 99%
“…Our current paper also reports on additional field sampling results that were unavailable at the time of our prior work [Ball et al, 1997a]. More specifically, new coring data have been obtained from several nearby locations [Mackay et al, 1997;Ball et al, 1998], now allowing us to provide comparative estimation results by applying a forensic model to both the prior and new data sets.…”
mentioning
confidence: 99%
See 3 more Smart Citations